Multicriterial Analysis of Simulated Process of Post-Combustion Capture of Pure H2S and Mixtures of H2S and CO2 Using Single and Blended Aqueous Alkanolamines - Allan N Soriano; Adonis P Adornado; Angelica A Pajinag; Diana Joy F. Acosta; Niel M Averion; Gilfred M Leron; Vergel C Bungay (ASEAN Journal of Chemical Engineering, 2015)
The paper evaluates the performance of the nine selected alkanolamines, namely, monoethanolamine (MEA), diethanolamine (DEA), monomethylethanolamine (MMEA), aminoethylethanolamine (AEEA), diisopropanolamine (DIPA), triethanolamine (TEA), dimethylethanolamine (DMEA), N-methyldiethanolamine (MDEA), and piperazine (PZ) for post-combustion capture of pure hydrogen sulfide (H2S) and mixtures of hydrogen sulfide and carbon dioxide (CO2) at different solvent mass flows: 500, 750, and 1000 kg/h using Aspen Plus® Version 7.2. The objective of the paper is to select the best chemical absorbent for each different criterion: percent H2S removal, percent H2S solvent carrying capacity, percent H2S retained in the lean solvent, percent CO2 and H2S removal, percent CO2 and H2S solvent carrying capacity, percent CO2 and H2S retained in the lean solvent. Based from the obtained results, piperazine is an absorbent that has a good potential for use as a single amine or in mixtures with other amines for capture of pure H2S and mixtures of H2S and CO2.